COMPETENŢA DE A LUA DECIZII MANAGERIALE - USM ADMIN (Moldova State University, 2010)
The quotidian situation requires increasingly the head-masters of pre-university educational institutions to possess managerial competences. This requires special training. We suggest this article in order to help head-masters to form skills, without which they cannot efficiently execute their managerial functions. This article contains the analysis of competences, their structure according to the sphere of managerial activity and it determinates the methodology of forming a competence, based on the example of decision-making ability.